Social developments in the European Union 2000. Second annual report = Bilan social de l'Union européenne 2000. Second rapport annuel (Brussels, 2001)
The first is the results of the Lisbon Summit held in March and, in particular, its impact on the European employment strategy. Secondly, the report could hardly omit to offer a detailed analysis of the Social Agenda adopted at the Nice European Summit in December and which defines – for the period until at least 2003, when it may be revised – the European Union’s social policy priorities. The third development relates to social security concerns, with special reference to the fight against social exclusion and poverty on the one hand and the future of retirement pensions on the other. The last area of focus is the enlargement of the EU to the countries of central and eastern Europe, a development which is giving rise to an increasing number of questions, particularly as regards its social implications. The analysis and evaluation of these four important areas of concern offers insight into the rationales and dynamics currently at work in the European institutions in the social policy field.